(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Natron has been used for thousands of years as a cleaning product for both the home and body. In the present study, the effects of five natron varieties farar kanwa, jar kanwa, manda, unguru and mangul sampled from famous Kano, Kurmi market were determined. Cadmium and Lead concentrations in blood samples of the wistar rats were determined following standard protocols Sub-acute toxicity of five natron samples were evaluated on 11 groups of Wistar albino rats of 3 per group each which were administered natron at various concentrations of 150mg/kg& 300mg/kg in each variety with the exception of control group. Values of Cd in blood ranged from 0.03-0.09µg/dL and for Pb ranged from 0.02 to 0.07µg/dL, which were below average values of CDC which were 5.00µg/dL and 1.26µg/dL for Cd and Pb respectively. However, histopathological examination of wistar rat liver and kidney tissues revealed alteration in their morphological features, as vascular congestion and fibrosis were observed in most sections examined.